Inventing entertainment : the player piano and the origins of an American musical industry - Dolan, Brian, 1970- (Rowman & Littlefield Publishers, 2009)
Brian Dolan's social and cultural history of the music business in relation to the history of the player piano is a critical chapter in the story of contemporary life. The player piano made the American music industry-and American music itself-modern. Foryears, Tin Pan Alley composers and performers labored over scores for quick ditties destined for the vaudeville circuit or librettos destined for the Broadway stage. But, the introduction of the player piano in the early 1900s, transformed Tin Pan Alley's guild of composers, performers, and theater owners into a music industry. The player pia.